MNK1 inhibitor CGP57380 overcomes mTOR inhibitor-induced activation of eIF4E: the mechanism of synergic killing of human T-ALL cells - Huang Xian-bo; Yang Chun-mei; Han Qing-mei; Ye Xiu-jin; Lei Wen; Qian Wen-bin (Acta Pharmacologica Sinica, 2018)
Although the treatment of adult T-cell acute lymphoblastic leukemia (T-ALL) has been signiﬁcantly improved, the heterogeneous genetic landscape of the disease often causes relapse. Aberrant activation of mammalian target of rapamycin (mTOR) pathway in T-ALL is responsible for treatment failure and relapse, suggesting that mTOR inhibition may represents a new therapeutic strategy. In this study, we investigated whether the mTOR complex 1 (mTORC1) inhibitor everolimus could be used as a therapeutic agent against human T-ALL. We showed that rapamycin and its analog RAD001 (everolimus) exerted only mild inhibition on the viability of Jurkat, CEM and Molt-4 cell lines (for everolimus the maximum inhibition was